+0  
 
0
221
1
avatar+4690 

Help.

 Nov 3, 2017
 #1
avatar+98090 
+2

√-28  = √ [ -1 * 4 * 7 ]  =  √  i^2  * √4 * √7  =  i * 2 * √7  =  2i√7

 

 

 

(5 - 5i) - ( -6 - 3i) =

 

5 - 5i + 6 + 3i  =

 

11 - 2i

 

 

(- 2 - 2i ) (-4 + 6i )  =

 

- (2 + 2i) ( -4 + 6i)  =

 

- [ 2*-4 +  ( 2i * -4)  + (2 * 6i)  + (  2*6*i^2) ]

 

Remember, NSS...i^2  = -1

 

- [ -8 - 8i + 12i +  12 (-1) ]  =

 

- [ -8 + 4i - 12 ]  =

 

- [ 4i - 20 ]  =

 

20 - 4i

 

 

 

cool cool cool

 Nov 3, 2017

30 Online Users

avatar
avatar
avatar
avatar
avatar